On multilevel codes and iterative multistage decoding. - Martin, P.A (IEEE Transactions on communications)
This paper develops an approach to iterative multistage decoding of multilevel codes. This involves passing reliability information to previous and subsequent decoders instead of only hard decisions to subsequent decoders. The paper also develops an adaptive version of the suboptimal soft output decoding algorithm of Picart and Pyndiah (1996). This adaptive algorithm provides a gain of approximately 0.24 dB at a bit error rate (BER) of 10-5 after four iterations and approximately 0.43 dB after ten iterations over the algorithm of Picart et al. If the adaptive algorithm is used in conjunction with iterative multistage decoding then a gain of approximately 0.62 dB is obtained at a BER of 10-5 after four iterations and approximately 0.9 dB after ten iterations over the algorithm of Picart et al